ANALYSIS OF RESEARCH ON DEVELOPMENT OF DNSSEC ON THE INTERNET - Fesokha, Vitalii; Fesokha , Nadiia (Ukrainian Information Security Research Journal, 2021)
The domain name system is an integral part of addressing on the Internet. Disadvantages in the implementation of the DNS protocol allow it to be used for malicious actions, during which the integrity and availability of data may be violated when exchanging data between the DNS client and the DNS server. DNSSEC technology is designed to protect the integrity of DNS data exchange, which prevents DNS clients from receiving false data. The article examines the current state of use of DNSSEC domain name enhancement technology and discusses the demand for DNSSEC deployment indicators and the problems that currently exist with obtaining the fullest possible understanding of the scale of deployment of this protocol on the Internet. DNSSEC allows domain name owners to use the method of digitally signing the information they enter into the DNS domain name system. This provides consumer protection, as DNS data that has been corrupted, accidentally or with malicious intent, does not reach them. Question addressed by DNSSEC: Can DNS answers be trusted? Since 2010, it has been possible to use the DNSSEC signature at the top level of the DNS, called the root, which greatly facilitates the global deployment of DNSSEC. However, even ten years later, the pace of DNSSEC implementation remains low. The article presents the current state, comparative analysis, problems and prospects of implementation of this technology for the protection of information resources. The relative complexity of the technology and the lack of ready-made solutions at the level of Internet users constrain the pace of DNSSEC implementation. At the same time, this is due to the additional costs of telecommunications operators and service providers for administration, as well as the lack of DNSSEC support for operator-level equipment and domain name registrars. DNS security should be an integral part of the plan to ensure the security of all Internet users, because the system, whose main task is to convert the names of network nodes into IP addresses, are used by virtually all applications and services on the network.